STUDENT INITIATIVES AS A COMPONENT OF UNIVERSITY CULTURE - Тормахова, Анастасія (Ukrainian Cultural Studies, 2023)
The university, as an educational center, had great cultural significance in European cities since the Middle Ages. These institutions were not just centers of knowledge, they also played a crucial role in attracting resources, both intellectual and economic, to the city. The article outlines the types of student initiatives implemented in the university space. It is emphasized that higher education institutions are centers where interaction between different participants – students, teachers, and administration – is possible in an informal way. Nowadays university is a space in which integration of students in an informal atmosphere takes place through student initiatives. As an integral part of campus life, they also contribute to the development of creativity, leadership, and civic engagement. The purpose of the study is to analyze the role and importance of student initiatives as a component of university culture. Results: Participation in various associations allows students to communicate with people who have similar interests and hobbies. Inclusion in the university culture helps bridge the gap between students from different faculties or departments by facilitating communication and potential cooperation. Any project can prove to its participants that social change is achievable and can be initiated by anyone, even a freshman. The main thing is to have a clear idea of your project’s goals, understand the requirements for its implementation, and enlist the necessary support from fellow students, teachers, and university management. It has been found that the result of student initiatives is participation in various creative associations, such as clubs, orchestras, choirs, or dance groups. Scientific and sports associations are also possible. Quite often it leads to organizing various volunteer projects aimed at meeting the urgent needs of society. A wide range of initiatives that students can organize relate to environmental, political, inclusion, or economic hackathons. In recent years, the practice of forming student initiatives for improving the quality of higher education has also spread. Student initiatives are a source of enriching the communicative experience between participants in the educational process and the transformation of university culture and society in general.